(untitled) (International Journal of Engineering and Computer Science, 2017)
Present world faces lots of problems and they have no time to concentrate in each and every work in their busy schedule, our robot is designed to perform the application of library control operations. It is mainly focused on detection of book and check for the availability of the book and by using GSM technology the user being in membership can be able to check out whether the book is present or not without their arrival to the library. when the person enters the required book in the PC by using line following sensor the book from the shelf is searched through RFID tag and the arm of the robot is made to extend were the book is fetched using the gripper which is designed by sensor operated motors and give it to the person also when the person returns the book the robot keeps the book back to its respective place book here the process of searching the book is made easier without the help of human. In case if the book is not available it can be identified in the database system the information of non-availability of the book is sent as message in the mobile to the user. Since we maintain database system we ensure that the library items stored properly in order to maintain their security thus the main purpose of the robot is to manage library daily operations efficiently.